Optimalisasi Subsidi LPG Sesuai Data NIK dan Pendistribusian LPG: Studi Kasus pada PT Gas Sembilan Semangat - M. Salim Bahreisy; Siti Ning Farida (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The targeted distribution of subsidized LPG remains a challenge for the government and distributors in Indonesia. This article examines PT Gas Sembilan Semangat's efforts to optimize the distribution of subsidized LPG by utilizing integrated administration of Citizen Identification Number (NIK) data. The study was conducted during an internship program in August-October 2024 using a descriptive approach, including data collection, verification, and distribution monitoring through digital applications such as Si Melon and MyPertamina. The findings show that valid NIK data and real-time distribution monitoring contribute to improved transparency and efficiency in the distribution process. However, challenges such as human errors in data entry and limited stock tracking were identified. Therefore, recommendations are proposed to develop database integration systems and enhance employee training. By optimizing administration and distribution processes, PT Gas Sembilan Semangat can support government policies in distributing subsidized LPG more equitably and accountably.